The spiritual experiences of students of Iran University of Medical Sciences in 2020 - Nasibeh Zerangian; Abbas Rohani; Mahboobeh Khosravani; Neda Khalili Samani; Marzieh Heydari; Zahra Rahimi Khalifeh Kandi; Morteza Mansourian (Shahid Beheshti University of Medical Sciences, 2022)
Background: Psychologists consider the acceptance of spirituality as a cultural reality and by acknowledging the positive effects of spirituality on mental health, the World Health Organization also considers the spiritual dimension as the physical, social and emotional dimensions of human existence. Spirituality is a genuine and inner experience that It lies in the nature of every human being. The purpose of this study was to investigate the spiritual experiences of students of Iran University of Medical Sciences in 2020. Methods: The present study was descriptive-analytical. The sample size of 500 students of Iran University of Medical Sciences in 2020 was estimated. For sampling, a list of students was prepared from the faculty education and the sample was selected by regular random sampling method through random number generation software. The data collection tool was a questionnaire with demographic questions and spiritual experiences. The collected data were analyzed after completion with SPSS 20 software. A significance level of 0.05 was considered. Results: The mean score of the meaning-finding component in life was obtained at 57.98. There was a significant relationship between spiritual experiences and gender, age and educational level of students, while no significant relationship was found between spiritual experiences and marital status and residence. Conclusion: In order to ensure the spiritual health of students, it is necessary to plan properly to create a meaningful atmosphere in universities for different age and gender groups.